An inosine triphosphate pyrophosphatase safeguards plant nucleic acids from aberrant purine nucleotides. Issue 5 (29th December 2022) - Straube, Henryk; Straube, Jannis; Rinne, Jannis; Fischer, Lisa; Niehaus, Markus; Witte, Claus‐Peter; Herde, Marco
Summary: In plants, inosine is enzymatically introduced in some tRNAs, but not in other RNAs or DNA. Nonetheless, our data show that RNA and DNA from Arabidopsis thaliana contain (deoxy)inosine, probably derived from nonenzymatic adenosine deamination in nucleic acids and usage of (deoxy)inosine triphosphate (dITP and ITP) during nucleic acid synthesis. We combined biochemical approaches, LC–MS, as well as RNA‐Seq to characterize a plant INOSINE TRIPHOSPHATE PYROPHOSPHATASE (ITPA) from A. thaliana, which is conserved in many organisms, and investigated the sources of deaminated purine nucleotides in plants. Inosine triphosphate pyrophosphatase dephosphorylates deaminated nucleoside di‐ and triphosphates to the respective monophosphates. ITPA loss‐of‐function causes inosine di‐ and triphosphate accumulation in vivo and an elevated inosine and deoxyinosine content in RNA and DNA, respectively, as well as salicylic acid (SA) accumulation, early senescence, and upregulation of transcripts associated with immunity and senescence. Cadmium‐induced oxidative stress and biochemical inhibition of the INOSINE MONOPHOSPHATE DEHYDROGENASE leads to more IDP and ITP in the wild‐type (WT), and this effect is enhanced in itpa mutants, suggesting that ITP originates from ATP deamination and IMP phosphorylation. Inosine triphosphate pyrophosphatase is part of a molecular protection system in plants, preventing the accumulation of (d)ITP and its usage for nucleic acid synthesis.